Preparing footballers for the next step: An intervention program from an ecological perspective - Larsen, C. H.; Alfermann, A.; Henriksen, K.; Christensen, M. K. (The Sport Psychologist, 2014)
The purpose of this article is to present practitioners and applied researchers with specific details of an ecological-inspired program and intervention in a professional football (soccer) club in Denmark. Based on an ecological agenda, the aim is to reinforce the culture of psychosocial development in the daily practice of a professional football academy, provide the skills required to succeed at the professional level and create stronger relations between the youth and professional departments. The authors suggest six principles as fundamental governing principles to inform an intervention inspired by the holistic ecological perspective. Descriptions of the intervention program and findings are presented in four interconnected steps. Insights are provided into delivery of workshops, the supervision of the coach, on-pitch training, evaluation of the program, and integrating sport psychology as a part of the culture within the club.